FROM MONOLITH TO MICROSERVICES: A PRACTICAL GUIDE TO LEGACY APPLICATION MODERNIZATION - Kowsick Venkatachalapathi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article comprehensively examines legacy application modernization, focusing on the transition from monolithic architectures to microservices. The article explores strategic approaches, technical implementations, and best practices in modernizing enterprise systems while maintaining business continuity. Through analysis of industry practices and case studies, we investigate the challenges and solutions in implementing Spring Boot and Spring Cloud frameworks, along with the evolution of DevOps practices and infrastructure management. The article addresses critical aspects, including data management strategies, service communication patterns, and security implementations in distributed systems. Examine the importance of organizational readiness, technical excellence, and risk mitigation strategies in successful modernization initiatives. The article provides insights into containerization, orchestration, and automation practices while highlighting the significance of comprehensive assessment and planning phases. The findings demonstrate that successful modernization requires a balanced approach combining technical expertise, organizational change management, and strategic planning methodologies, ultimately improving system scalability, reliability, and business agility.